No more Mr. fat guy the nutrition and fitness programme for men! - Savill, Jonathan; Smedley, Richard (Vermilion, 2000)
What makes his programme so different is that it shows you how to acquire a healthier lifestyle through sensible eating and exercise that will keep your weight down infefinately. how to use exercise as a tool to help you loose weight, how to cope when eating out or in a social situation and even contains mouthwatering recipe suggestions.